P2-S2.01 Support groups as a strategy for reducing HIV vulnerability among female sex workers in Bellary, Northern Karnataka, India. (10th July 2011) - Chintada, D R; Pillai, P; Mahadevapappa, S; Mohammed, P; Isac, S; Ramesh, B M; Ramappa, V; Bhattacharjee, P; Moses, S
Abstract : Background: The Karnataka Health Promotion Trust implements HIV preventive interventions for female sex workers (FSWs) in Karnataka, South India, in partnership with non-governmental and community-based organizations (NGOs and CBOs). These interventions are supported by the Bill & Melinda Gates Foundation. Community mobilisation and collectivisation are key vulnerability reduction strategies. In Bellary district, FSWs are encouraged to form site-level groups of 10–12 members which meet regularly. They discuss STIs, HIV, condom negotiation skills, and other important issues. They also support members during crises, and engage in savings and credit activities. We attempted to understand the impact in Bellary of collective membership and the availability of economic support on two measures of safer sex behaviour: clinic attendance and condom use with last client. Methods: Multivariate logistic regression was used to measure the association between the outcome variables and collective membership, using data from a round of integrated behavioural and biological assessments conducted in Bellary in 2008. We also conducted focus group discussions (FGDs) with members and non- members of collectives, to understand the reasons for observed associations. Results: 34% of FSWs were members of collectives. Members were 7 times more likely to have used condoms with their last client (adjusted OR [AOR]: 7.5, 95% CI 1.9 to 30.1, p<0.05). Additionally, collective members were 4 times more likely to visit an STI clinic than non-members (AOR: 4.6, 95% CI 2.0 to 10.6, p<0.05). FGDs revealed that alternate sources of economic activity, such as savings enhancement and low interest loans to collective members, reduced sex workers' dependence on exploitative sources of credit, enabling them to better negotiate condom use with clients who resisted unprotected sex. Further, the sex worker collectives helped FSWs to overcome their fears of stigmatisation, creating a more enabling environment that positively influenced access to clinics for STI care. Conclusions: Membership in site-level groups considerably increased access of FSWs to program services. Activities to address the economic vulnerability of female sex workers were key factors in enabling greater condom use. Savings and access to credit helped FSWs to reduce their dependency on sex work, and enabled them to more readily negotiate condom use with clients.